How the spirit became God: the mosaic of early Christian pneumatology - Hughes, Kyle R. (Cascade Books, 2020)
The problem of the Holy Spirit -- The Spirit and divine testimony -- The Spirit and Christian identity -- The Spirit and person language -- The Spirit and the divine economy -- The Spirit and full divinity -- The invitation of the Holy Spirit.